A tiered analytical approach for target, non-target and suspect screening analysis of polar transformation products of polycyclic aromatic compounds. (November 2019) - Schemeth, Dieter; Nielsen, Nikoline J.; Andersson, Jan T.; Christensen, Jan H.
Abstract: Polycyclic aromatic compounds (PACs) possess toxicity towards humans, and their presence in the environment is unwanted. Polar transformation products (TPs) are more mobile, and can be considered emerging contaminants, as they represent a more bioavailable carrier of the same toxic properties. Acidic TPs has been proposed as an important class of polar TPs. This study presents a tiered analytical approach to investigate acidic and polar PAC TPs in environmental conditions. The tiered approach exploits target analysis for quantification of acids; suspect screening for tentative identification based on retention time and spectral matching using databases; and finally non-target analysis based on chromatography and data independent broadband MS to highlight potentially unknown analyte peaks. The approach includes a mixed-mode anion exchange solid phase extraction (MAX-SPE) to fractionate neutral and acidic compounds, and is applied to three cases: I) Photo-oxidation of six PACs generated suspected hydroxylated-, carbonylated- and carboxylated PACs but also proposed the presence of mono- and dicarboxylic acids, which have not been reported elsewhere. For a subset of four acids, conversion rates were determined. II) Recovery of spiked acids from diesel spilled harbor water was 80% by LC-MS, and diesel spill weathering was evaluated from the neutral fraction by GC-MS. III) By non-target analysis sulfonated PACs, presumable derived from photo-oxidation, were detected in run-off basins of an arctic landfarm, alongside hypothesized naturally occuring fatty acids. The tiered approach is a sensitive and versatile tool to extract information on PACs and their polar TPs from polluted environmental sites. Graphical abstract: Image 1 Highlights: Tiered analytical approach to investigate PAC transformation using GC-MS and LC-MS/MS. Group-type fractionation into neutral and aromatic mono- and dicarboxylic acids. Postulation of polar mono- and dicarboxylic acid by non-targeted analysis. Discovery of sulfonated PACs and carboxylic compounds in polluted arctic samples. Determination of PAC conversion rates under simulated sunlight radiation.